Vasoactive intestinal polypeptide: a putative transmitter in the canine gastric muscularis mucosa. - Angel, F (1983)
The nature of the inhibitory transmitter in the canine gastric muscularis mucosae was studied in vitro using superfusion techniques. The inhibitory effect of nerve stimulation (10 V, 200 mus, 10 Hz) was not altered by adrenergic, cholinergic or serotonergic antagonists. Adenosine triphosphate had no effect on spontaneous mechanical activity. Nucleotide pyrophosphatase and apamin had no effect on the response to nerve stimulation. Alpha-chymotrypsin abolished the inhibitory effect of nerve stimulation. Radioimmunoassay of the muscle indicated the presence of gastrin/cholecystokinin-substance P- and vasoactive intestinal polypeptide (VIP)-like immunoreactivity. Of the three peptides present, only VIP produced a concentration-dependent relaxation. A substance with VIP-like immunoreactivity was released during nerve-induced relaxation of the muscle, and its release was blocked by tetrodotoxin and calcium-depleted solution. The inhibitory effect of nerve stimulation was abolished by VIP antiserum. These data strongly support the hypothesis that VIP or a closely related peptide is an inhibitory neurotransmitter in the canine gastric muscularis mucosae.